Metals contamination using Polymesoda Expansa (Marsh Clam) as bio-indicator in Kelantan river, Malaysia = Pencemaran logam di Sungai Kelantan, Malaysia menggunakan Polymesoda expansa (Lokan) sebagai penunjuk biologi - Ong, Meng Chuan; Kamaruzzaman, Muhammad Izzat; Yong, Jaw Chuen; Yunus, Kamaruzzaman; Bidai, Joseph (The Malaysian Analytical Sciences Society, 2017)
Bivalve, such as marsh clam (Polymesoda expansa) feed by filtering most of the suspended particle in water that surrounding them. Lots of elements being trap into their body via this feeding habit including pollutant such as trace metals. Unfortunately, these marsh clams were taken directly by human as their daily diet. Due to its ability to filter water, marsh clam was used to monitor the level of trace metals in aquatic system in significant place such as industrial area. Therefore, this study was carried out at Kelantan River near to the industrial area in Pengkalan Chepa, Kelantan, Malaysia. A total of 80 marsh clams were collected from 4 different sites to represent a different environmental condition. The in-toto of the marsh clam were dissected and digest with suprapur nitric acid by using Teflon Bomb method. Six metals were determined by using Inductively Coupled Plasma Mass Spectrometry including chromium, iron, copper, cadmium, lead and zinc. The highest mean concentration of all metals studied (Cr 45.03 μg/g dry weight; Fe 1.28 μg/g dry weight; Cu 21.8 μg/g dry weight; Cd 1.15 μg/g dry weight; Pb 2.31 μg/g dry weight; Zn 898 μg/g dry weight) in the marsh clam tissue was recorded at station 4 which is near to the industrial area discharge. Whereas, those concentration were lower at Station 1 and Station 2, which located at the upstream and far from the industrial area discharge. On the other hand, the size of marsh clam does not significantly correlate to the concentration of selected trace metals. Level of selected metals in some the samples were exceeded the permissible limit provide by Malaysia Food Safety and Food Regulation 1985 especially marsh clam collected from station near to industrial area. Therefore, marsh clam collected for consumption near to industrial area need to be continuously monitor to prevent any acute effect on human health risk.